Research on the Development of Advertising Industry under the Trend of AI Application - Pan, Ying (Transactions on Economics, Business and Management Research, 2024)
The rapid advancement of artificial intelligence (AI) is transforming the advertising industry by enhancing precision, personalization, and operational efficiency. AI’s ability to analyze consumer behavior in real time allows for highly targeted advertising, while machine learning algorithms optimize ad delivery and content generation. Despite these benefits, the integration of AI also introduces challenges such as data privacy concerns, algorithmic biases, and potential reductions in creative originality. This research explores the advancement of advertising and marketing under AI application patterns, intending to assess both the benefits and the obstacles presented by modern AI technologies. By analyzing present techniques and problems, the research seeks to offer recommendations for leveraging AI efficiently while dealing with arising issues and incorporating strategies such as the bolstering of data privacy protections, the rectification of algorithmic prejudices, the synchronization of artificial intelligence with human creativity, the enhancement of AI’s cultural sensitivity and emotional intelligence, and the optimization of methodologies employed in evaluating advertising efficacy. The findings will certainly provide beneficial insights for industry experts, tech developers, and policymakers to navigate the progressing landscape and ensure lasting development in the AI-driven marketing field.